Boosting the performance of a Reverse Electrodialysis – Multi-Effect Distillation Heat Engine by novel solutions and operating conditions. (1st November 2019) - Ortega-Delgado, B.; Giacalone, F.; Cipollina, A.; Papapetrou, M.; Kosmadakis, G.; Tamburini, A.; Micale, G.
Graphical abstract: Highlights: A RED-MED heat engine with NaCl & KAc solutions at high temperature is simulated. Potassium acetate leads to better performance than sodium chloride. Increasing the solution temperature in the RED unit improves the overall efficiency. A maximum thermal efficiency of almost 10% can be achieved. Abstract: This work presents a performance analysis of a waste-heat-to-power Reverse Electrodialysis Heat Engine (RED-HE) with a Multi-Effect Distillation (MED) unit as the regeneration stage. The performance of the system is comparatively evaluated using two different salts, sodium chloride and potassium acetate, and investigating the impact of different working solutions concentration and temperature in the RED unit. For both salt solutions, the impact of membrane properties on the system efficiency is analysed by considering reference ionic exchange membranes and high-performing membranes. Detailed mathematical models for the RED and MED units have been used to predict the thermal efficiency of the closed-loop heat engine. Results show that, under the conditions analysed, potassium acetate provides higher efficiency than sodium chloride, requiring a smaller MED unit (lower number of effects). The maximum thermal efficiency obtained is 9.4% (43% exergy efficiency) with a RED operating temperature of 80 °C, KAc salt solution, adopting high-performing ion exchange membranes, and with 12 MED effects. This salt has been identified as more advantageous than sodium chloride from a thermodynamic point of view for the RED-HE technology and is also recommended for a cost-effective technology implementation.